LISTENING STRATEGIES IN LANGUAGE LEARNING AND THEIR TEACHING PRACTICE IN SERBIA - Mićić, Софија; Čajka, Зоран (Наслеђе, 2013)
Listening is one of the basic language skills in language learning. Language learning depends on listening to a great extent, because listening enables students to interact in oral communication. There is a need for understanding the listening strategies at all levels of language acquisition. Students need to grasp the strategies and rely on them in their language learning. Every learner should be given an adequate training and expert guided practice in using listening strategies. Teaching of listening skills is still the weak spot in the language teaching process in our country. Despite students having mastered the elements of English grammar and vocabulary, their listening comprehension is often substantially deficient. The most salient point that has become noticeable is students’ insufficient or limited listening comprehension skills.